2003
DOI: 10.1063/1.1533831
|View full text |Cite
|
Sign up to set email alerts
|

Thin films of double perovskite Sr2FeMoO6: Growth, optimization, and study of the physical and magnetotransport properties of films grown on single-crystalline and polycrystalline SrTiO3 substrates

Abstract: Thin films of Sr2FeMoO6 have been deposited on single-crystalline and polycrystalline SrTiO3 substrates by pulsed laser deposition from a stoichiometric target. In order to obtain high-quality films, the deposition parameters were systematically optimized. The films grown under optimized conditions show properties comparable to those of bulk Sr2FeMoO6 single crystals. Surprisingly, polycrystalline films obtained by depositing on polycrystalline SrTiO3 substrates do not show any significant low-field magnetores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 24 publications
6
41
0
Order By: Relevance
“…Such insulator role can be played also by the oxygen incorporated at grain boundaries. This slow and reversible process takes place at room temperature [13,46], generating an instability of grain boundary interfaces exposed to dry air. The resistivity of our SFMO samples is thus influenced by the following factors: grain sizes which determine the proportion of grain boundaries, connections between the grains and the instability of grain boundary interfaces (by slow incorporation of oxygen).…”
Section: Resistivitymentioning
confidence: 99%
“…Such insulator role can be played also by the oxygen incorporated at grain boundaries. This slow and reversible process takes place at room temperature [13,46], generating an instability of grain boundary interfaces exposed to dry air. The resistivity of our SFMO samples is thus influenced by the following factors: grain sizes which determine the proportion of grain boundaries, connections between the grains and the instability of grain boundary interfaces (by slow incorporation of oxygen).…”
Section: Resistivitymentioning
confidence: 99%
“…Highest onset T C values of the thin films prepared in optimized deposition atmosphere and temperature were about 375 K, even though T C of the target used in deposition of these films was around 400 K [11]. With other deposition atmospheres T C over room temperature have been achieved, but not proven values close to 400 K [12][13][14][15]. One of the possible reasons for changes in the magnetic properties between the polycrystalline and the thin-film samples growth by PLD can be the anti-site disorder (ASD) in which Fe and Mo transpose.…”
Section: Introductionmentioning
confidence: 94%
“…Advantages of PLD are that it does not require a very high vacuum during the deposition and a stoichiometric target can be used [9,10]. Commonly used atmosphere in the deposition of SFMO thin films is oxygen [10,[12][13][14], but vacuum, Ar, N 2 , or mixture of these with O 2 and H 2 are also used [13][14][15]. The choice of the deposition atmosphere has a crucial role in the deposition process as well as the deposition temperature.…”
Section: Introductionmentioning
confidence: 98%
“…More commonly used deposition atmosphere is oxygen [8,[11][12][13], but it has been shown that an oxygen backround pressure higher than 10 −4 mbar leads to impurity phases [8]. In addition to impurities, the anti-site disorder (ASD), where Fe and Mo transpose their positions in the lattice, together with possible oxygen vacancies have a strong deteriorating effect on the magnetic properties of the SFMO thin films [14][15][16].…”
Section: Introductionmentioning
confidence: 99%